Implementasi Pelayanan Lintas Budaya Dalam Gereja Berdasarkan Kisah Para Rasul 10:34-43 - Priska Natonis; Sabda Budiman; Jamin Tanhidy (Pascasarjana IAKN Manado, 2022)
Cross-cultural evangelism is the duty of all believers without exception. In Acts 10 there is an interesting phenomenon related to cross-cultural ministry. In this verse it is recorded that the apostle Peter was given an assignment by God through a vision to go to Cornelius' place, to preach about Jesus. Cornelius was a Greek while the apostle Peter was a Jew. The Apostle Peter was a Jew who held firmly to Jewish customs. This shows the existence of cross-cultural services that occur. This article aims to describe the implementation of cross-cultural services based on Acts 10:34-43. The author uses descriptive qualitative research methods by analyzing data such as books and journals. From the results of the analysis, the writer finds that the church needs to introduce Christ as a God who loves everyone, proclaims that everyone has the right to receive salvation, conveys the message of peace through Jesus Christ to everyone, and conveys the message of peace through Jesus Christ to everyone. The church's awareness of the Great Commission of the Lord Jesus, one of which is to implement cross-cultural services, especially in terms of evangelism.